Creepella von Cacklefur meet me in horrorwood - STILTON, GERONIMO; GERONIMO STILTON (New York Scholastic Inc, 2011)
Gorgo, the monster in Cacklefur Castle's moat, is in love with the famouse monster movie star Blobbina.
Keywords: the Shivery News and lives in Mysterious Valley